Suffering and happiness in Turkish folk poetry in the context of positive psychology: The examples of Asik Mahzuni Serif and Neset Ertas - Güven, Ahmet Zeki; Arslan, Gökmen (Frontiers in Psychology, 2023)
The widespread adoption of positive psychology at the beginning of the century has fortified the scholarly foundations of “happiness.” Thus, researchers have focused on “happiness” rather than “suffering” in boosting the joy of life within positive psychology, aiming for individuals to achieve peace with themselves and society. With the developments in positive psychology, over recent years, the idea of integrating both positive and negative aspects of human nature to build a better life for oneself and others has contributed to the rise of second-wave positive psychology (PP 2.0). The present study aimed to explore suffering and happiness in Turkish folk culture through a sample of poems by Asik Mahzuni Serif and Neset Ertas. The study results indicated that suffering-themed concepts were mentioned more than happiness-themed concepts. Within the theme of suffering, the world was the most frequently mentioned concept in Mahzuni’s works. He emphasizes in his works that the world is the source of many sufferings. In Ertas’s poems, moreover, love was found to be the most frequently mentioned suffering-themed concept. Ertas considers love to be the most significant source of suffering. It was also determined that while separation is the least used concept in the theme of suffering in Mahzuni’s verses, it is never mentioned in Ertas’s poems. Other concepts pointing to the theme of suffering are poverty, ignorance, longing, death, and slavery. We found that the theme of happiness is mentioned much less frequently than the theme of suffering. While the most used happiness-themed concept is misery/remedy, in Mahzuni’s words, love is cited in Ertas’s poems. Expressing the view that suffering can be an opportunity for people, Mahzuni emphasizes in his poems that people can grow by learning lessons from their suffering. Ertas, moreover, sees love as the most important source of happiness. The other concepts referencing happiness in the poems were friend, mother, soft answer, and spring. Overall, the results suggest that suffering is an important source of building resilience, which, in turn, can produce happiness. People can grow with the help of the experience of suffering so that this experience can contribute to their flourishing.